Lens Fibrosis: Understanding the Dynamics of Cell Adhesion Signaling in Lens Epithelial-Mesenchymal Transition - Taiyab, Aftab; West-Mays, Judith (Frontiers in Cell and Developmental Biology, 2022)
Injury to the ocular lens perturbs cell-cell and cell-capsule/basement membrane interactions leading to a myriad of interconnected signaling events. These events include cell-adhesion and growth factor-mediated signaling pathways that can ultimately result in the induction and progression of epithelial-mesenchymal transition (EMT) of lens epithelial cells and fibrosis. Since the lens is avascular, consisting of a single layer of epithelial cells on its anterior surface and encased in a matrix rich capsule, it is one of the most simple and desired systems to investigate injury-induced signaling pathways that contribute to EMT and fibrosis. In this review, we will discuss the role of key cell-adhesion and mechanotransduction related signaling pathways that regulate EMT and fibrosis in the lens.